Optimization of the catalytic ozonation process using copper oxide nanoparticles for the removal of benzene from aqueous solutions - L. Mohammadi; E. Bazrafshan; M. Noroozifar; A.R. Ansari-Moghaddama; A.R. Khazaei Feizabad; A.H. Mahvi (Global Journal of Environmental Science and Management, 2017)
The current study aimed to examine the overall feasibility of the use of copper oxide nanoparticles (CuO-NPs) as a catalyst in ozonation process for the removal of benzene from aqueous solutions under experimental conditions. This experimental study was conducted on a laboratory scale reactor in a semi-batch mode. The effect of critical operating parameters such factors as pH, concentration of benzene, reaction time and nano-catalyst dose on the removal of benzene was investigated. The samples included with benzene concentrations (10-200 mg/L), pH (3-13), catalyst dose (0.1-0.5 mg), and ozonation time (5-50 min). Findings indicated that the removal of benzene depended on various utilization parameters. The highest efficiency was achieved at reaction time of 50 min, pH of 12, initial benzene concentration of 10 mg/L and catalyst dose of 0.5 g. Among the studied factors, the maximum and the minimum contributions were made by the dose of nanoparticles (83%) and the reaction time (~73%). The software predicted that use of 0.13 g of the catalyst at pH of 12 and ozonation time of 5 min would lead to a removal efficiency of 68.4%. The catalytic ozonation process was able to remove benzene, and addition of CuO-NPs as a catalyst together with the ozonation process increased the benzene removal efficiency. The values of R2 = 0.9972, adjusted R2= 0.9946, and predicted R2 =0.9893 indicated that the model was acceptably predicted by the software and fitted the data obtained in the experiments.